A Case Report of BAP1-inactivated Melanocytoma with Discussion of Possible Dual Roles of BAP1 Loss in Tumorigenesis - Guo, MD, PhD, Lili; Andea, MD, MBA, Aleodor (Doru) A.; Chen, MD, PhD, MBA, Frank; Goldenberg, MD*, Alicia V. (North American Journal of Medicine and Science, 2025)
BRCA1-associated protein (BAP1) is a tumor suppressor involved in a myriad of cellular processes. BAP1-inactivated melanocytomas (BIMs) are rare melanocytic tumors characterized by the loss of nuclear expression of BAP1. Here, we report a case of a 33-year-old female presenting with a cutaneous macule on the left lateral nasal wall. Histopathological examination revealed a dermal-based melanocytic neoplasm comprised of large epithelioid melanocytes with pleomorphic nuclei, some with multinucleation. Due to the morphology atypia, melanoma was suspected. However, PRAME (PReferentially expressed Antigen in MElanoma) immunohistochemical staining was negative, and further BAP1 staining showed loss of nucleus expression. Chromosomal microarray confirmed the loss of chromosome 3 (including BAP1) and chromosome X. Compared with malignant melanoma, most BIMs follow indolent courses. We further discussed the possible molecular pathogenesis of BIMs and propose that although the loss of BAP1 predisposes melanocytes to form tumor, it may hinder the development of more malignant forms. Hence, BAP1 may emerge as an interesting target for exploring synthetic lethality to better understand melanoma pathogenesis. [N A J Med Sci. 2025;18(1):009-012. DOI: 10.7156/najms.2025.1801009] Key Words: BRCA1-associated protein (BAP1), BAP1-inactivated melanocytomas (BIMs), tumorigenesis